Successful outcome of surgical reintervention for implant placement in borderline aesthetic area related to agenesis: a case report (Research, Society and Development, 2022)
The aim of this study is to illustrate and discuss the fundamentals of a well-succeeded and minimally invasive technique of surgical reintervention for installing implant in the reduced area of the alveolus, affected by agenesis, and traumatized by an unsuccessful intervention. Materials and methods: A 27-year-old patient sought dental care and her main cause was the great dissatisfaction with the aesthetic sequelae in the region of the right upper lateral incisor, in addition to the uncertainty regarding the predictability of a new unitary implant. Imaging exams showed trauma in the middle and apical region of the canine root surface. The dimensions of the edentulous area varied between 4.6 and 5.52 mm. A small diameter implant (BLT 2.9mm SC, Loxim SLActive® 12 mm, TiZr - Straumann Dental Implant System) was planned and installed, in addition to a subepithelial connective graft. Results: The results achieved allowed to restore the desired function and aesthetics, with excellence, low morbidity, in addition to a predictability favored by the benefits related to small diameter implants. Conclusions: The concept of minimally invasive dentistry is becoming an effective surgical approach and, although these implants present a higher risk for fracture than do large-diameter implants, implant fractures are rarely observed.